Building gypsum high ductility cement-based composite material and preparation method and device thereof
By using building gypsum to replace part of cement and mixing it with other materials in a mixer, a high-ductility cement-based composite material of building gypsum was prepared, which solved the problems of large shrinkage and significant volume of existing materials, and improved the refractory and mechanics of the materials. Performance, achieving more efficient waste utilization and environmental protection effects.
Patent Information
- Application Number
- CN202411117275.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The existing high-ductile cement-based composite materials have defects of large shrinkage and significant volume, which limits their widespread use and promotion in actual engineering applications. At the same time, the utilization rate of desulfurization gypsum is insufficient, resulting in environmental pollution problems.
Use building gypsum to replace part of the cement, and prepare β-semi-water gypsum by drying and heating desulfurization gypsum, and combine it with silicate cement, fly ash, finely ground blast furnace slag powder, quartz sand, polyvinyl alcohol fiber and other materials. Mix evenly in the mixer to prepare a high-ductile cement-based composite of building gypsum.
It reduces carbon emissions in the cement production process, improves waste utilization, and reduces land pollution. At the same time, the material has lower shrinkage, better fire resistance and better mechanical properties.
Smart Images

Figure CN118637882B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to building materials and relates to the technical field of concrete, in particular to a building gypsum high-ductility cement-based composite material and a preparation method and device thereof. Background Art
[0002] High-ductility cement-based composite materials are made of cement, mineral admixtures, silica sand and other matrix materials mixed with some fibers, and have excellent mechanical properties. Its characteristics include high ultimate tensile strain, high tensile strength, high toughness and high fracture resistance, and show obvious stress hardening characteristics. Under saturation, the material can form multiple cracks with a crack spacing of less than 3mm, and the ultimate tensile strain can reach more than 3% (about 150 times that of traditional concrete). This material has multiple close-seam steady-state cracking characteristics and excellent crack width control ability. It performs well in structural reinforcement, can eliminate concrete spalling caused by stress concentration, improve the bearing capacity of the structure, and effectively prevent harmful substances from invading the interior of the component through cracks, protecting the steel bars from corrosion. Therefore, high-ductility cement-based composite materials have shown broad application prospects in fields such as civil engineering and rapid road repair.
[0003] Desulfurized gypsum is a byproduct produced by thermal power plants and other enterprises in the process of coal combustion, after SO2 gas and smoke are treated by desulfurization equipment or isolation pre-washing circulation method. In recent years, with the increasingly stringent environmental protection regulations and the promotion of desulfurization technology, my country has produced more than 100 million tons of desulfurized gypsum each year. However, its utilization rate has not yet reached 80%. The large amount of desulfurized gypsum stockpiling not only occupies a large amount of land resources, but also causes serious pollution to the surrounding environment and groundwater, becoming an environmental problem that needs to be solved urgently.
[0004] Green and sustainable development is the core hotspot in the field of building materials research. Developing the resource utilization of solid waste is an important way to achieve green and sustainable development. How to make large-scale resource utilization of desulfurized gypsum has become an urgent problem to be solved. In addition, the existing high-ductility cement-based composite materials have the defects of large shrinkage and large volume, which limit its widespread use and promotion in practical engineering applications. Summary of the invention
[0005] The purpose of the present invention is to provide a high-ductility cement-based composite material for building gypsum and a preparation method and device thereof, so as to solve the problem of how to utilize desulfurized gypsum and the defects of large shrinkage and large volume of existing high-ductility cement-based composite materials proposed in the above background technology.
[0006] The technical scheme adopted by the present invention is as follows: the high-ductility cement-based composite material of building gypsum is prepared from the following raw materials in parts by weight: 100-200 parts of silicate cement, 200-255 parts of fly ash, 200-325 parts of ground blast furnace slag powder, 440-475 parts of quartz sand, 800-950 parts of building gypsum, 20-30 parts of polyvinyl alcohol fiber, 5-10 parts of water reducer, 2-6 parts of retarder, 5-10 parts of waterproof powder, 2-4 parts of defoamer and 235-325 parts of water.
[0007] Wherein, the building gypsum is prepared by the following method:
[0008] Step 1: Dry and crush the desulfurization gypsum, an industrial byproduct produced by flue gas desulfurization in thermal power plants, to obtain waste gypsum powder;
[0009] Step 2: heating the waste gypsum powder in dry hot air at 180-200° C. for 2 hours to obtain β-hemihydrate gypsum, also known as building gypsum.
[0010] Secondly, the preparation method of the building gypsum high-ductility cement-based composite material disclosed in the present invention comprises the following steps:
[0011] Step 1: uniformly mix the silicate cement, fly ash, ground blast furnace slag powder, quartz sand and building gypsum in a mixer for 2-4 minutes to obtain a mixture;
[0012] Step 2: Add the retarder, water reducing agent, defoamer, waterproof powder and water to the mixture in sequence, stirring while adding, the water adding time is 1-2 minutes, and stirring is continued for 2-3 minutes after the water adding is completed to obtain a mixed slurry;
[0013] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 2-3 minutes to obtain an initial building gypsum-based composite material;
[0014] Step 4: mold, vibrate, shape and cure the initial building gypsum-based composite material to obtain a building gypsum high-ductility cement-based composite material.
[0015] The tensile strength of the polyvinyl alcohol fiber is 1550-1850 MPa, the shear length is 3 mm, the diameter is 15-31 μm, the elongation is 3-10%, the elastic modulus is 35-50 GPa, and the density is 1.28-1.31 g / cm 3 .
[0016] The fly ash and ground blast furnace slag powder are industrial wastes, and their main chemical components include silicon dioxide, aluminum oxide, calcium oxide, and iron oxide.
[0017] Wherein, the water reducing agent is a polycarboxylic acid water reducing agent, and the water reducing rate is greater than 25%.
[0018] The retarder is a plant protein gypsum retarder, which is a milky white solid powder.
[0019] Wherein, the waterproof powder is a polysiloxane solid powder.
[0020] Wherein, the defoamer is an industrial-grade defoamer, which is a white solid powder.
[0021] Wherein, the particle size of the quartz sand is 0.075-0.18 mm.
[0022] Furthermore, a preparation device for the above-mentioned high-ductility cement-based composite material of building gypsum is disclosed, comprising a shell, the inner cavity of the shell is spherical in shape, a feed pipe is connected to the shell; a discharge pipe is connected to the shell; a rotating shaft is rotatably connected to the shell, the rotating shaft is connected to a first motor through a transmission mechanism, and the first motor is connected to the shell; a foldable and expandable stirring component is installed on the side wall of the rotating shaft located in the shell, the folded stirring component is used to stir concrete, and the expanded stirring component is used to scrape off residues on the inner wall of the shell.
[0023] A conical bucket is provided at the upper end of the feed pipe; an end cover is provided on the conical bucket, a feeding port is provided on the end cover, a quantitative feeding mechanism is provided on the feeding port, the quantitative feeding mechanism includes a bearing platform, the bearing platform is composed of legs and a top plate; a matrix-arranged pressure sensor is provided on the top plate, a pressing plate is provided on the pressure sensor, and a matrix-arranged vertical rod is provided on the top surface of the pressing plate; a conical hopper is provided on the vertical rod, the conical hopper is used to store raw materials, and a strap is provided on the top surface of the conical hopper; a feed pipe is provided on the strap, one end of the feed pipe enters the lower part of the conical hopper, the other end of the feed pipe is connected to the feeding port, and a vacuum pump is provided on the side wall of the feed pipe; a second valve is provided on the side wall of the feed pipe, and the second valve is located between the vacuum pump and the feeding port.
[0024] A bypass pipe is provided on the bridle plate, one end of the bypass pipe enters into the conical hopper, the other end of the bypass pipe is connected to the feed pipe, the connection point is located between the vacuum pump and the second valve, and a third valve is provided on the side wall of the bypass pipe.
[0025] The beneficial effect of the present invention is that the present invention uses building gypsum to replace part of cement, which can not only reduce carbon emissions in the cement production process, but also improve the utilization rate of waste and reduce land pollution. At the same time, the main component of building gypsum is calcium sulfate hemihydrate, which will undergo a hydration reaction after mixing with water to generate calcium sulfate dihydrate. The volume of calcium sulfate dihydrate generated by hydration remains basically unchanged, while products such as calcium hydroxide and hydrated calcium silicate generated by cement hydration are prone to water loss and shrinkage during the hardening process, and the gaps between building gypsum crystals are small, which reduces the volume shrinkage caused by water evaporation. The thermal conductivity of building gypsum materials is low, which means that the heat transfer speed is slow, which can effectively delay the spread of fire, and the dehydration process of building gypsum is a strong endothermic reaction, which can absorb a large amount of heat, thereby delaying the temperature rise and providing good fire resistance. During the hydration process, building gypsum generates a fine and regular needle-shaped or columnar crystal structure. These crystals can interweave to form a dense microstructure, which helps to improve the strength and toughness of the material. In addition, the hydration reaction speed is fast, and a solid skeleton with high strength can be quickly formed, which enables building gypsum-based materials to have better mechanical properties at an early stage. Therefore, building gypsum high-ductility cement-based composite materials have lower shrinkage, better fire resistance and better mechanical properties than cement-based high-ductility cement. Therefore, the building gypsum high-ductility cement-based composite materials disclosed in this application have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the main cross-sectional structure of the preparation device.
[0027] Figure 2 Schematic diagram of the three-dimensional structure of the preparation device.
[0028] Figure 3 It is a schematic diagram of the three-dimensional structure of the conical bucket.
[0029] Figure 4 It is a schematic diagram of the three-dimensional structure of the pressing sleeve.
[0030] Figure 5 It is a schematic diagram of the main cross-sectional structure of the groove on the shaft.
[0031] Figure 6 It is a schematic diagram of the main structure of the shaft and fan blades.
[0032] Figure 7 This is a schematic diagram of the three-dimensional structure of the first fan blade.
[0033] Figure 8 This is a schematic diagram of the three-dimensional structure of the second fan blade.
[0034] Fig. 9 It is a schematic diagram of the main cross-sectional structure of the first sliding block.
[0035] Fig.10 This is a schematic diagram of the three-dimensional structure of the second fan blade.
[0036] Fig.11 It is a schematic diagram of the three-dimensional structure of the second slider and the third slider.
[0037] Fig.12 This is a schematic diagram of the three-dimensional structure after the four fan blades are folded.
[0038] Fig.13 It is a schematic diagram of the three-dimensional structure of the first return spring and the second return spring.
[0039] Fig.14 It is a schematic diagram of the main cross-sectional structure of the wedge block.
[0040] Fig.15 It is a schematic diagram of the side cross-sectional structure of the wedge block.
[0041] Fig.16 It is a schematic diagram of the main cross-sectional structure of the arc tube.
[0042] Fig.17 It is a schematic diagram of the main structure of the conveying pipe.
[0043] Fig.18 It is a schematic diagram of the main cross-sectional structure of the conical hopper.
[0044] Fig.19 It is a schematic diagram of the main cross-sectional structure of the bypass pipe.
[0045] In the figure: 1, shell; 2, feed pipe; 3, discharge pipe; 4, rotating shaft; 5, transmission mechanism; 6, first motor; 7, stirring assembly; 8, foot seat; 9, first hemispherical shell; 10, second hemispherical shell; 11, flange; 12, conical bucket; 13, fixing ring; 14, hinge; 15, cover; 16, first convex seat; 17, second convex seat; 18, pressing sleeve; 19, positioning bolt; 20, rocker; 21, groove; 22, countersunk hole; 23, telescopic rod; 24, traction rope; 25, rotating rod; 26, positioning nut; 27, fan blade; 28, sleeve; 29, arc groove; 30, connecting ear; 31, first screw; 32, second screw; 33, first slider; 34, third screw; 35, second slider; 36, fourth screw; 37, third slider; 38, fifth screw; 39, first composite spring; 40, second return spring; 41, limit bolt; 42, sink; 43, wedge block; 44, tension spring; 45, arc tube; 46, anti-blocking cap; 47, cover; 48, first spring; 49, plug; 50, drain trough; 51, flow channel; 52, shaft seat; 53, water injection head; 54, sealed bearing; 55, delivery pipe; 56, gas storage tank; 57, gas delivery pipe; 58, air generator generator; 59, branch pipe; 60, water storage tank; 61, first valve; 62, end cover; 63, feeding port; 64, quantitative feeding mechanism; 65, supporting platform; 66, supporting leg; 67, top plate; 68, pressure sensor; 69, pressing plate; 70, vertical rod; 71, cone hopper; 72, bridging board; 73, feeding pipe; 74, vacuum pump; 75, second valve; 76, bypass pipe; 77, third valve. DETAILED DESCRIPTION
[0046] Embodiments of the present invention are described in detail below. Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0047] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the present invention.
[0048] In addition, the terms "first", "second", "third", "fourth" and "fifth" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features.
[0049] In the description of the present invention, it should be noted that, unless otherwise clearly stipulated and limited, the terms "installation", "connection" and "connection" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0050] The high-ductility cement-based composite material of building gypsum is prepared from the following raw materials in parts by weight: 100-200 parts of silicate cement, 200-255 parts of fly ash, 200-325 parts of ground blast furnace slag powder, 440-475 parts of quartz sand, 800-950 parts of building gypsum, 20-30 parts of polyvinyl alcohol fiber, 5-10 parts of water reducer, 2-6 parts of retarder, 5-10 parts of waterproof powder, 2-4 parts of defoaming agent and 235-325 parts of water.
[0051] Wherein, the building gypsum is prepared by the following method:
[0052] Step 1: Dry and crush the desulfurization gypsum, an industrial byproduct produced by flue gas desulfurization in thermal power plants, to obtain waste gypsum powder;
[0053] Step 2: heating the waste gypsum powder in dry hot air at 180-200° C. for 2 hours to obtain β-hemihydrate gypsum, also known as building gypsum.
[0054] Making desulfurized gypsum into building gypsum not only has a simple preparation process, but also can improve strength and reduce dependence on natural gypsum resources, with high economic benefits. The main chemical components of building gypsum are calcium oxide and sulfur trioxide.
[0055] Preferably, the polyvinyl alcohol fiber has a tensile strength of 1550-1850 MPa, a shear length of 3 mm, a diameter of 15-31 μm, an elongation of 3-10%, an elastic modulus of 35-50 GPa, and a density of 1.28-1.31 g / cm 3 .
[0056] Preferably, the fly ash and ground blast furnace slag powder are industrial wastes, and the main chemical components include silicon dioxide, aluminum oxide, calcium oxide, and iron oxide.
[0057] Preferably, the water reducer is a polycarboxylate water reducer with a water reduction rate of >25%.
[0058] Preferably, the retarder is a plant protein gypsum retarder, which is a milky white solid powder.
[0059] Preferably, the waterproof powder is a polysiloxane solid powder.
[0060] Preferably, the defoamer is an industrial grade defoamer, a white solid powder.
[0061] Preferably, the particle size of the quartz sand is 0.075-0.18 mm.
[0062] Preferably, the water is ordinary tap water that meets the requirements of the "Standard for Water Use in Concrete" (JGJ63-2016).
[0063] Secondly, the present invention discloses a method for preparing a high-ductility cement-based composite material of building gypsum, comprising the following steps:
[0064] Step 1: uniformly mix the silicate cement, fly ash, ground blast furnace slag powder, quartz sand and building gypsum in a stirring device for 2-4 minutes to obtain a mixture;
[0065] Step 2: Add the retarder, water reducing agent, defoamer, waterproof powder and water to the mixture in sequence, stirring while adding, the water adding time is 1-2 minutes, and stirring is continued for 2-3 minutes after the water adding is completed to obtain a mixed slurry;
[0066] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 2-3 minutes to obtain an initial building gypsum-based composite material;
[0067] Step 4: mold, vibrate, shape and cure the initial building gypsum-based composite material to obtain a building gypsum high-ductility cement-based composite material.
[0068] The present invention will be further described below through specific embodiments.
[0069] Example 1: A high-ductility cement-based composite material of building gypsum is composed of the following raw materials in parts by mass: 120 parts of silicate cement, 210 parts of fly ash, 240 parts of ground blast furnace slag powder, 455 parts of quartz sand, 850 parts of building gypsum, 23 parts of polyvinyl alcohol fiber, 6 parts of water reducer, 3 parts of retarder, 6 parts of waterproof powder, 2 parts of defoaming agent, and 255 parts of water.
[0070] Wherein, the building gypsum is prepared by the following method:
[0071] Step 1: Dry and crush the desulfurization gypsum, an industrial byproduct produced by flue gas desulfurization in thermal power plants, to obtain waste gypsum powder;
[0072] Step 2: heating the waste gypsum powder in dry hot air at 185°C for 2 hours to obtain β-hemihydrate gypsum, also known as building gypsum.
[0073] The tensile strength of the polyvinyl alcohol fiber is 1810 MPa, the shear length is 3 mm, the diameter is 16 μm, the elongation is 7%, the elastic modulus is 40 GPa, and the density is 1.29 g / cm 3 .
[0074] As mentioned above, fly ash and ground blast furnace slag powder are industrial wastes. The main chemical components of fly ash are 48.01% silicon dioxide, 20.11% aluminum oxide, 8.94% calcium oxide, and 6.23% iron oxide. The main chemical components of ground blast furnace slag powder are 35.65% silicon dioxide, 14.23% aluminum oxide, 31.98% calcium oxide, and 0.93% iron oxide.
[0075] A method for preparing a high-ductility cement-based composite material of building gypsum comprises the following steps:
[0076] Step 1: uniformly mix the silicate cement, fly ash, ground blast furnace slag powder, quartz sand and building gypsum in a mixer for 2 minutes to obtain a mixture;
[0077] Step 2: Add the retarder, water reducing agent, defoamer, waterproof powder and water to the mixture in sequence, stirring while adding, the water adding time is 1 minute, and stirring is continued for 2 minutes after the water adding is completed to obtain a mixed slurry;
[0078] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 2 minutes to obtain an initial building gypsum-based composite material;
[0079] Step 4: mold, vibrate, shape and cure the initial building gypsum-based composite material to obtain a building gypsum high-ductility cement-based composite material.
[0080] Example 2: A high-ductility cement-based composite material of building gypsum is composed of the following raw materials in parts by mass: 150 parts of silicate cement, 235 parts of fly ash, 290 parts of ground blast furnace slag powder, 470 parts of quartz sand, 880 parts of building gypsum, 25 parts of polyvinyl alcohol fiber, 7 parts of water reducer, 4 parts of retarder, 8 parts of waterproof powder, 3 parts of defoaming agent, and 285 parts of water.
[0081] Wherein, the building gypsum is prepared by the following method:
[0082] Step 1: Dry and crush the desulfurization gypsum, an industrial byproduct produced by flue gas desulfurization in thermal power plants, to obtain waste gypsum powder;
[0083] Step 2: heating the waste gypsum powder in dry hot air at 190° C. for 2 hours to obtain β-hemihydrate gypsum, also known as building gypsum.
[0084] The tensile strength of the polyvinyl alcohol fiber is 1810 MPa, the shear length is 3 mm, the diameter is 16 μm, the elongation is 7%, the elastic modulus is 40 GPa, and the density is 1.29 g / cm 3 .
[0085] As mentioned above, fly ash and ground blast furnace slag powder are industrial wastes. The main chemical components of fly ash are 48.01% silicon dioxide, 20.11% aluminum oxide, 8.94% calcium oxide, and 6.23% iron oxide. The main chemical components of ground blast furnace slag powder are 35.65% silicon dioxide, 14.23% aluminum oxide, 31.98% calcium oxide, and 0.93% iron oxide.
[0086] A method for preparing a high-ductility cement-based composite material of building gypsum comprises the following steps:
[0087] Step 1: uniformly mix the silicate cement, fly ash, ground blast furnace slag powder, quartz sand and building gypsum in a stirring device for 3 minutes to obtain a mixture;
[0088] Step 2: Add the retarder, water reducing agent, defoamer, waterproof powder and water to the mixture in sequence, stirring while adding, the water adding time is 1 minute, and stirring is continued for 3 minutes after the water adding is completed to obtain a mixed slurry;
[0089] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 3 minutes to obtain an initial building gypsum-based composite material;
[0090] Step 4: mold, vibrate, shape and cure the initial building gypsum-based composite material to obtain a building gypsum high-ductility cement-based composite material.
[0091] Example 3: A high-ductility cement-based composite material of building gypsum is composed of the following raw materials in parts by mass: 100 parts of silicate cement, 205 parts of fly ash, 310 parts of ground blast furnace slag powder, 470 parts of quartz sand, 920 parts of building gypsum, 28 parts of polyvinyl alcohol fiber, 9 parts of water reducer, 5 parts of retarder, 9 parts of waterproof powder, 4 parts of defoaming agent, and 300 parts of water.
[0092] Wherein, the building gypsum is prepared by the following method:
[0093] Step 1: Dry and crush the desulfurization gypsum, an industrial byproduct produced by flue gas desulfurization in thermal power plants, to obtain waste gypsum powder;
[0094] Step 2: heating the waste gypsum powder in dry hot air at 195° C. for 2 hours to obtain β-hemihydrate gypsum, also known as building gypsum.
[0095] The tensile strength of the polyvinyl alcohol fiber is 1810 MPa, the shear length is 3 mm, the diameter is 16 μm, the elongation is 7%, the elastic modulus is 40 GPa, and the density is 1.29 g / cm 3 .
[0096] As mentioned above, fly ash and ground blast furnace slag powder are industrial wastes. The main chemical components of fly ash are 48.01% silicon dioxide, 20.11% aluminum oxide, 8.94% calcium oxide, and 6.23% iron oxide. The main chemical components of ground blast furnace slag powder are 35.65% silicon dioxide, 14.23% aluminum oxide, 31.98% calcium oxide, and 0.93% iron oxide.
[0097] A method for preparing a high-ductility cement-based composite material of building gypsum comprises the following steps:
[0098] Step 1: uniformly mixing the silicate cement, fly ash, ground blast furnace slag powder, quartz sand and building gypsum in a stirring device for 4 minutes to obtain a mixture;
[0099] Step 2: Add the retarder, water reducing agent, defoamer, waterproof powder and water to the mixture in sequence, stirring while adding, the water adding time is 2 minutes, and stirring is continued for 3 minutes after the water adding is completed to obtain a mixed slurry;
[0100] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 3 minutes to obtain an initial building gypsum-based composite material;
[0101] Step 4: mold, vibrate, shape and cure the initial building gypsum-based composite material to obtain a building gypsum high-ductility cement-based composite material.
[0102] Comparative Example 1: A high-ductility cement-based composite material of building gypsum is composed of the following raw materials in parts by weight: 120 parts of silicate cement, 210 parts of fly ash, 240 parts of ground blast furnace slag powder, 455 parts of quartz sand, 23 parts of polyvinyl alcohol fiber, 6 parts of water reducer, 3 parts of retarder, and 255 parts of water.
[0103] The tensile strength of the polyvinyl alcohol fiber is 1810 MPa, the shear length is 3 mm, the diameter is 16 μm, the elongation is 7%, the elastic modulus is 40 GPa, and the density is 1.29 g / cm 3 .
[0104] As mentioned above, fly ash and ground blast furnace slag powder are industrial wastes. The main chemical components of fly ash are 48.01% silicon dioxide, 20.11% aluminum oxide, 8.94% calcium oxide, and 6.23% iron oxide. The main chemical components of ground blast furnace slag powder are 35.65% silicon dioxide, 14.23% aluminum oxide, 31.98% calcium oxide, and 0.93% iron oxide.
[0105] A method for preparing a high-ductility cement-based composite material of building gypsum comprises the following steps:
[0106] Step 1: uniformly mix the silicate cement, fly ash, ground blast furnace slag powder and quartz sand in a stirring device for 2 minutes to obtain a mixture;
[0107] Step 2: Add the retarder, water reducing agent and water to the mixture in sequence, stirring while adding, the water adding time is 1 minute, and stirring is continued for 2 minutes after the water adding is completed to obtain a mixed slurry;
[0108] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 2 minutes to obtain an initial cement-based composite material;
[0109] Step 4: The initial cement-based composite material is molded, vibrated, formed, and cured to obtain a high-ductility cement-based composite material.
[0110] Comparative Example 2, a high-ductility cement-based composite material of building gypsum is composed of the following raw materials in parts by mass: 150 parts of silicate cement, 235 parts of fly ash, 290 parts of ground blast furnace slag powder, 470 parts of quartz sand, 25 parts of polyvinyl alcohol fiber, 7 parts of water reducer, 4 parts of retarder, and 285 parts of water.
[0111] The tensile strength of the polyvinyl alcohol fiber is 1810 MPa, the shear length is 3 mm, the diameter is 16 μm, the elongation is 7%, the elastic modulus is 40 GPa, and the density is 1.29 g / cm 3 .
[0112] As mentioned above, fly ash and ground blast furnace slag powder are industrial wastes. The main chemical components of fly ash are 48.01% silicon dioxide, 20.11% aluminum oxide, 8.94% calcium oxide, and 6.23% iron oxide. The main chemical components of ground blast furnace slag powder are 35.65% silicon dioxide, 14.23% aluminum oxide, 31.98% calcium oxide, and 0.93% iron oxide.
[0113] A method for preparing a high-ductility cement-based composite material of building gypsum comprises the following steps:
[0114] Step 1: uniformly mix the silicate cement, fly ash, ground blast furnace slag powder and quartz sand in a stirring device for 3 minutes to obtain a mixture;
[0115] Step 2: Add the retarder, water reducing agent and water to the mixture in sequence, stirring while adding, the water adding time is 1 minute, and stirring is continued for 3 minutes after the water adding is completed to obtain a mixed slurry;
[0116] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 3 minutes to obtain an initial cement-based composite material;
[0117] Step 4: The initial cement-based composite material is molded, vibrated, formed, and cured to obtain a high-ductility cement-based composite material.
[0118] Comparative Example 3, a high-ductility cement-based composite material of building gypsum is composed of the following raw materials in parts by mass: 100 parts of silicate cement, 205 parts of fly ash, 310 parts of ground blast furnace slag powder, 470 parts of quartz sand, 28 parts of polyvinyl alcohol fiber, 9 parts of water reducer, 5 parts of retarder, and 300 parts of water.
[0119] The tensile strength of the polyvinyl alcohol fiber is 1810 MPa, the shear length is 3 mm, the diameter is 16 μm, the elongation is 7%, the elastic modulus is 40 GPa, and the density is 1.29 g / cm 3 .
[0120] As mentioned above, fly ash and ground blast furnace slag powder are industrial wastes. The main chemical components of fly ash are 48.01% silicon dioxide, 20.11% aluminum oxide, 8.94% calcium oxide, and 6.23% iron oxide. The main chemical components of ground blast furnace slag powder are 35.65% silicon dioxide, 14.23% aluminum oxide, 31.98% calcium oxide, and 0.93% iron oxide.
[0121] A method for preparing a high-ductility cement-based composite material of building gypsum comprises the following steps:
[0122] Step 1: uniformly mix the silicate cement, fly ash, ground blast furnace slag powder and quartz sand in a stirring device for 4 minutes to obtain a mixture;
[0123] Step 2: Add the retarder, water reducer and water to the mixture in sequence, stirring while adding, the water adding time is 2 minutes, and stirring is continued for 3 minutes after the water adding is completed to obtain a mixed slurry;
[0124] Step 3: adding the polyvinyl alcohol fiber to the mixed slurry and stirring for 3 minutes to obtain an initial cement-based composite material;
[0125] Step 4: The initial cement-based composite material is molded, vibrated, formed, and cured to obtain a high-ductility cement-based composite material.
[0126] The high ductility cement-based composite materials obtained by adding the building gypsum of Examples 1 to 3 were respectively used as experimental groups 1-3, and the high ductility cement-based composite materials obtained by Comparative Examples 1 to 3 without adding building gypsum, waterproof powder and defoaming agent components were used as control groups 1-3. The 28d compressive strength, tensile strength, density, autogenous shrinkage deformation and drying shrinkage deformation of the experimental groups 1-3 and the control groups 1-3 were measured. The drying shrinkage deformation test method of all high ductility cement-based composite materials of the present invention is implemented in accordance with the GB / T 29417-2012 standard, the autogenous shrinkage deformation test method is implemented in accordance with the JTG3420-2020 standard, and the compressive and tensile strength test methods are implemented in accordance with the JC / T 2461-2018 standard. The test results are shown in Table 1. Compared with control groups 1-3, the compressive strength of the building gypsum high-ductility cement-based composite materials (experimental groups 1-3) prepared by the present invention is increased by 10-47%, the tensile strength is increased by 8-36%, the density is reduced by 20-42%, the autogenous shrinkage deformation is reduced by 63-76%, and the drying shrinkage is reduced by 54-63%.
[0127] Table 1 Test results of high ductility cement-based composites
[0128]
[0129] like Figure 1 As shown, further, considering that concrete residues are easy to remain on the inner wall of the mixer, if they are not treated, crusting and solidification will occur, affecting the subsequent normal mixing, and therefore a preparation device for the above-mentioned building gypsum high-ductility cement-based composite material is disclosed, including a shell 1, the inner cavity shape of the shell 1 is spherical, and a feed pipe 2 is connected to the shell 1; a discharge pipe 3 is connected to the shell 1; a rotating shaft 4 is rotatably connected to the shell 1, and the rotating shaft 4 is connected to a first motor 6 through a transmission mechanism 5, and the first motor 6 is connected to the shell 1. The transmission mechanism 5 can select any one of belt drive, chain drive and gear drive; a foldable and expandable stirring component 7 is installed on the side wall of the rotating shaft 4 located in the shell 1, and the folded stirring component 7 is used to stir concrete, and the unfolded stirring component 7 is used to scrape off the residue on the inner wall of the shell 1; the present application sets a deformable stirring component 7, which cooperates with the spherical inner cavity, and can completely scrape off the residue on the inner wall of the shell 1 on the basis of mixing, with good cleaning effect, ensuring the subsequent normal mixing.
[0130] like Figure 2As shown, further, considering the influence of the structure and installation position of the shell 1 on the scraping residue, the shell 1 is preferably arranged at an angle, tilted 45° counterclockwise; it also includes a foot seat 8 supporting the shell 1, and the shape of the foot seat 8 is preferably L-shaped, and the foot seat 8 is located at a position deviating from the center just below the shell 1; the feed pipe 2 is preferably located at the upper center position of the shell 1, and the lower end of the feed pipe 2 cannot extend into the shell 1, so as to avoid structural interference between the stirring assembly 7 and the feed pipe 2; the discharge pipe 3 is located at the lower center position of the shell 1, and the upper end of the discharge pipe 3 cannot extend into the shell 1, so as to avoid structural interference between the stirring assembly 7 and the discharge pipe 3.
[0131] like Figure 3 As shown, further, the shell 1 includes a first hemispherical shell 9 and a second hemispherical shell 10, the first hemispherical shell 9 and the second hemispherical shell 10 are connected by a flange 11, the first hemispherical shell 9 is located above the second hemispherical shell 10, the feed pipe 2 is located on the first hemispherical shell 9, and the discharge pipe 3 is located on the second hemispherical shell 10. By setting a detachable shell 1, it is easy to inspect and maintain.
[0132] like Figure 3 As shown, further, the upper end of the feed pipe 2 is connected with a conical bucket 12.
[0133] like Figure 4 As shown, further, the lower end of the discharge pipe 3 is connected to a fixing ring 13, a hinge 14 is installed on the fixing ring 13, the other end of the hinge 14 is connected to a cover body 15, the cover body 15 is buckled and matched with the fixing ring 13, a first boss 16 is connected to the cover body 15, and the first boss 16 and the hinge 14 are in a relative position; a second boss 17 is connected to the fixing ring 13, a pressing sleeve 18 is hinged on the second boss 17, the shape of the pressing sleeve 18 is U-shaped, and a positioning bolt 19 is threadedly connected to the horizontal section of the pressing sleeve 18, the positioning bolt 19 is used to press the first boss 16, and a rocker 20 is connected to the positioning bolt 19, and the rocker 20 is rotated to make the positioning bolt 19 press or loosen the first boss 16, thereby realizing the switch control of the discharge pipe 3.
[0134] like Figure 5~Figure 12As shown, further, a groove 21 is provided on the side wall of the rotating shaft 4 in the housing 1; a countersunk hole 22 is provided on the rotating shaft 4, and the countersunk hole 22 is offset from the axis; the stirring assembly 7 includes a telescopic rod 23 provided on the countersunk hole 22, and the telescopic rod 23 can select a hydraulic cylinder or an air cylinder, and the piston end of the telescopic rod 23 is connected to a traction rope 24, and the traction rope 24 passes through the groove 21 to control the opening and closing of the fan blade 27; a rotating rod 25 is rotatably connected to the middle of the rotating shaft 4; positioning nuts 26 are screwed on both ends of the rotating rod 25; a plurality of fan blades 27 are rotatably connected to the rotating rod 25, and the fan blades 27 of this scheme There are 4 blades 27 arranged in sequence. The shape of the blade 27 is one eighth of a circular plate. The arc section of the blade 27 is adapted to the inner wall of the housing 1. A sleeve 28 is connected to the acute angle of the blade 27. The sleeve 28 is rotatably connected to the rotating rod 25. An arc groove 29 is opened at the waist of the blade 27. The arc groove 29 divides the blade 27 into two parts. The side of the blade 27 is connected to a connecting ear 30. The connecting ear 30 connects the two parts of the blade 27 into a whole; the connecting ear 30 of the first blade 27 is fixed to the rotating shaft 4 by a first screw 31; the connecting ear 31 of the second blade 27 is fixed to the rotating shaft 4 by a first screw 31; The first slider 33 is connected to the first fan blade 27 through the second screw 32, and the first slider 33 is slidably connected to the arc groove 29 of the first fan blade 27; the connecting ear 30 of the third fan blade 27 is connected to the second slider 35 through the third screw 34, and the second slider 35 is slidably connected to the arc groove 29 of the second fan blade 27; the connecting ear 30 of the fourth fan blade 27 is connected to the third slider 37 through the fourth screw 36, and the third slider 37 is slidably connected to the arc groove 29 of the third fan blade 27; another connecting ear 30 of the fourth fan blade 27 is connected to the traction rope 29 through the fifth screw 38 4 is connected, and the folding process: in the initial state, the four fan blades 27 are stacked together, so that the rotating shaft 4 can drive the fan blades 27 to stir; after the stirring is completed, the telescopic rod 23 is extended to drive the traction rope 24 to unfold the fourth fan blade 27, the third fan blade 27, and the second fan blade 27 in turn. After the four fan blades 27 are fully unfolded, a semicircular plate is formed, which is adapted to the inner wall of the shell 1, and the rotating shaft 4 rotates to scrape off all the residues on the inner wall of the shell 1, and then the telescopic rod 23 is retracted, the four fan blades 27 are stacked together, and the residues on the adjacent fan blades 27 can also be automatically cleaned.
[0135] like Fig.13 As shown, further, considering the resetting problem of the fan blade 27, a first resetting spring 39 is installed in the groove 21, and the first resetting spring 39 is used to drive the second fan blade 27 to reset. A second resetting spring 40 is installed in the groove 21, and the second resetting spring 40 is used to drive the third fan blade 27 to reset, thereby ensuring the folding and resetting of the fan blade 27.
[0136] like Fig.14 and Fig.15As shown, further, considering that the positions of the stacked blades 27 will change during stirring, thus affecting the stirring effect, the end face of the rotating shaft 4 is threadedly connected with a limiting bolt 41, and a sink groove 42 is provided on the rotating shaft 4, which is communicated with the groove 21, and a wedge block 43 is slidably connected to the sink groove 42. The inclined surface of the wedge block 43 is pressed and positioned with the arcuate edges of the four blades 27, and the position of the wedge block 43 is adjusted by the limiting bolt 41, and a tension spring 44 is installed between the wedge block 43 and the sink groove 42. By setting an adjustable wedge block 43, the positioning of the four blades 27 is facilitated, and the stability of stirring is ensured. When it is necessary to scrape off the residue, the limiting bolt 41 is loosened, and the wedge block 43 will loosen the four blades 27, so that the telescopic rod 23 can pull the blades 27 to unfold.
[0137] like Fig.16 and Fig.17 As shown, further, considering that the shell 1 needs to be cleaned regularly, so that the cleaning is more thorough, the side wall of the rotating shaft 4 in the shell 1 is connected with an arc tube 45, and the port of the arc tube 45 is installed with an anti-blocking cap 46; the anti-blocking cap 46 includes a cover body 47, a first spring 48, and a plug 49; the cover body 47 is connected to the arc tube 45 by threads, and the side wall of the cover body 47 is processed with a drainage groove 50, and a plug 49 is installed in the cover body 47, and the plug 49 is adapted to the pipe mouth of the arc tube 45, and a first spring 48 is installed between the plug 49 and the cover body 47. When the water pressure in the arc tube 45 is greater than the elastic force of the first spring 48, the water flow pushes the plug 49 away and enters the shell 1. When the water pressure in the arc tube 45 is less than the elastic force of the first spring 48, the first spring 48 pushes back the plug 49 to close the pipe mouth of the arc tube 45 to avoid concrete blockage. Plug or enter the arc tube 45; a flow channel 51 connected to the arc tube 45 is opened at the lower end of the rotating shaft 4; a shaft seat 52 is installed on the shell 1, and a water injection head 53 is rotatably connected to the shaft seat 52, and the water outlet of the water injection head 53 is connected to the flow channel 51 of the rotating shaft 4 through a sealing bearing 54, and the water inlet of the water injection head 53 is connected to an air tank 56 through a delivery pipe 55; the air tank 56 is connected to an air generator 58 through an air delivery pipe 57; a branch pipe 59 is connected to the delivery pipe 55, and a water tank 60 is connected to the branch pipe 59; a first valve 61 is connected to the side wall of the delivery pipe 55; air is injected into the air tank 56 through the air generator 58, and the first valve 61 is opened, so that the high-pressure gas drives the water in the water tank 60 to enter the arc tube 45, and the water pressure causes the plug 49 to be pushed open, and the shell 1, the rotating shaft 4, and the stirring assembly 7 are cleaned.
[0138] like Fig.18As shown, further, considering the feeding of raw materials and fibers, an end cover 62 is placed on the conical hopper 12, and a feeding port 63 is opened on the end cover 62. A quantitative feeding mechanism 64 is installed on the feeding port 63. The quantitative feeding mechanism 64 includes a bearing platform 65, and the bearing platform 65 is composed of a support leg 66 and a top plate 67. The upper surface of the top plate 67 is a horizontal plane; a matrix-arranged pressure sensor 68 is installed on the top plate 67, and the number of the pressure sensors 68 is at least 4. A pressing plate 69 is installed on the pressure sensor 68, and the upper surface of the pressing plate 69 is a horizontal plane. The top surface of the pressing plate 69 is welded with vertical rods 70 arranged in a matrix; a conical hopper 71 is welded on the vertical rod 70, and the conical hopper 71 is used to store raw materials. A strap 72 is welded on the top surface of the conical hopper 71, and the strap 72 is in the shape of a strip; a feed pipe 7 is welded on the strap 72. 3. One end of the feeding pipe 73 enters the lower part of the conical hopper 71, and the other end of the feeding pipe 73 is connected to the feeding port 63. A vacuum pump 74 is installed on the side wall of the feeding pipe 73, which can transport the raw materials from the conical hopper 71 to the conical hopper 12; a second valve 75 is installed on the side wall of the feeding pipe 73, and the second valve 75 is located between the vacuum pump 74 and the feeding port 63, which can control whether the raw materials are transported; feeding process: the operator first puts the raw material or fiber into the conical hopper 71, at this time the pressure sensor 68 displays a value, starts the vacuum pump 74 to start feeding, the above value is continuously reduced, when the value reaches the desired feeding amount, close the second valve 75, and the feeding stops; by setting the quantitative feeding mechanism 64, any weight of raw materials can be added to the shell 1, the operation is simple, and the feeding weight is accurate.
[0139] like Fig.19 As shown, further, considering that the above-mentioned multiple raw materials cannot be fully mixed when directly put into the conical hopper 71, which affects the stirring effect of the raw materials, a bypass pipe 76 is welded on the strap 72, one end of the bypass pipe 76 enters into the conical hopper 71, and the other end of the bypass pipe 76 is connected to the feed pipe 73, and the connection point is located between the vacuum pump 74 and the second valve 75. A third valve 77 is installed on the side wall of the bypass pipe 76. The circulation process is: close the second valve 75, open the third valve 77, start the vacuum pump 74, so that the raw materials in the conical hopper 71 enter the bypass pipe 76 from the feed pipe 73, and then return to the conical hopper 71 from the bypass pipe 76. The raw materials form a circulating flow, and the sufficient stirring and mixing of multiple raw materials are achieved.
[0140] Although the present invention has been described in detail with reference to the aforementioned examples, it is still possible for those skilled in the art to make and modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A device for preparing a high-ductility cement-based composite material of building gypsum, comprising a shell (1), characterized in that: The inner cavity of the shell (1) is spherical in shape. The shell (1) is connected to a feed pipe (2). The shell (1) is connected to a discharge pipe (3). The shell (1) is rotatably connected to a rotating shaft (4), and the rotating shaft (4) is connected to a first motor (6) via a transmission mechanism (5). A stirring assembly (7) is provided on the side wall of the rotating shaft (4) located in the shell (1), and a groove (21) is provided on the side wall of the rotating shaft (4) located in the shell (1). A countersunk hole (22) is provided on the rotating shaft (4), and the countersunk hole (22) is offset from the axis. The stirring assembly (7) includes a telescopic rod (23) provided on the countersunk hole (22), and a traction rope (24) is connected to the piston end of the telescopic rod (23). ); a rotating rod (25) is rotatably connected to the middle of the rotating shaft (4); positioning nuts (26) are screwed on both ends of the rotating rod (25); a plurality of fan blades (27) are rotatably connected to the rotating rod (25); the number of the fan blades (27) is 4, and the 4 fan blades (27) are arranged in sequence; the shape of the fan blade (27) is one eighth of a circular plate; the arc section of the fan blade (27) is adapted to the inner wall of the housing (1); a sleeve (28) is connected to the acute angle of the fan blade (27); the sleeve (28) is rotatably connected to the rotating rod (25); an arc groove (29) is provided at the waist of the fan blade (27); the arc groove (29) divides the fan blade (27) into two parts; the side of the fan blade (27) is connected to a connecting The connecting ear (30) connects the two parts of the fan blade (27) into a whole; the connecting ear (30) of the first fan blade is fixed to the rotating shaft (4) by a first screw (31); the connecting ear (30) of the second fan blade is connected to the first slider (33) by a second screw (32), and the first slider (33) is slidably connected to the arc groove (29) of the first fan blade; the connecting ear (30) of the third fan blade is connected to the second slider (35) by a third screw (34), and the second slider (35) is slidably connected to the arc groove (29) of the second fan blade; the connecting ear (30) of the fourth fan blade is connected to the third slider (35) by a fourth screw (36). 7), the third slider (37) is slidably connected to the arc groove (29) of the third fan blade; another connecting ear (30) of the fourth fan blade is connected to the traction rope (24) through a fifth screw (38); the end surface of the rotating shaft (4) is threadedly connected to a limit bolt (41), a sink groove (42) is provided on the rotating shaft (4), the sink groove (42) is connected to the groove (21), a wedge block (43) is slidably connected to the sink groove (42), the inclined surface of the wedge block (43) is pressed and positioned with the arc edges of the four fan blades (27), the position of the wedge block (43) is adjusted by the limit bolt (41), and a tension spring (44) is provided between the wedge block (43) and the sink groove (42).
2. The preparation device according to claim 1, characterized in that: The shell (1) is arranged tilted, tilted 45° counterclockwise; it also includes a foot seat (8) supporting the shell (1), the foot seat (8) being located at a position deviated from the center just below the shell (1); the feed pipe (2) is located at a position just above the center of the shell (1), and the discharge pipe (3) is located at a position just below the center of the shell (1).
3. The preparation device according to claim 1, characterized in that: The housing (1) comprises a first hemispherical shell (9) and a second hemispherical shell (10); the first hemispherical shell (9) and the second hemispherical shell (10) are connected via a flange (11); and the first hemispherical shell (9) is located above the second hemispherical shell (10).
4. The preparation device according to claim 1, characterized in that: A fixing ring (13) is provided at the lower end of the discharge pipe (3), a hinge (14) is provided on the fixing ring (13), a cover body (15) is provided at the other end of the hinge (14), the cover body (15) is buckled and matched with the fixing ring (13), a first convex seat (16) is provided on the cover body (15), and the first convex seat (16) and the hinge (14) are in a relative position; a second convex seat (17) is provided on the fixing ring (13), a pressing sleeve (18) is hinged on the second convex seat (17), the pressing sleeve (18) is in a U-shaped shape, and a positioning bolt (19) is threadedly connected to the horizontal section of the pressing sleeve (18), the positioning bolt (19) is used to press the first convex seat (16), and a rocker (20) is provided on the positioning bolt (19).
5. The preparation device according to claim 1, characterized in that: A first return spring (39) is arranged in the groove (21), and the first return spring (39) is used to drive the second fan blade to return to its original position. A second return spring (40) is arranged in the groove (21), and the second return spring (40) is used to drive the third fan blade to return to its original position.
6. The preparation device according to claim 1, characterized in that: The side wall of the rotating shaft (4) located in the housing (1) is connected to an arc-shaped tube (45), and an anti-blocking cap (46) is provided at the end of the arc-shaped tube (45); the anti-blocking cap (46) comprises a cover body (47), a first spring (48), and a plug (49); the cover body (47) and the arc-shaped tube (45) are connected by threads, and a drainage groove (50) is processed on the side wall of the cover body (47); a plug (49) is provided in the cover body (47), and the plug (49) is adapted to the tube mouth of the arc-shaped tube (45), and a first spring (48) is provided between the plug (49) and the cover body (47); a connection arc-shaped tube (45) is provided at the lower end of the rotating shaft (4). 45); a shaft seat (52) is provided on the housing (1); a water injection head (53) is rotatably connected to the shaft seat (52); a water outlet of the water injection head (53) is connected to the flow channel (51) of the rotating shaft (4) via a sealing bearing (54); a water inlet of the water injection head (53) is connected to an air storage tank (56) via a delivery pipe (55); the air storage tank (56) is connected to an air generator (58) via an air delivery pipe (57); a branch pipe (59) is connected to the delivery pipe (55), and the branch pipe (59) is connected to a water storage tank (60); and a first valve (61) is connected to the side wall of the delivery pipe (55).
7. A method for preparing a high-ductility cement-based composite material of building gypsum, using the preparation device according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: Dry and crush the desulfurization gypsum, an industrial byproduct produced by flue gas desulfurization in thermal power plants, to obtain waste gypsum powder; Step 2: heating the waste gypsum powder in dry hot air at 180-200° C. for 2 hours to obtain β-hemihydrate gypsum, also known as building gypsum; Step 3: Evenly mix silicate cement, fly ash, ground blast furnace slag powder, quartz sand and building gypsum in a stirring device for 2-4 minutes to obtain a mixture; Step 4: Add retarder, water reducing agent, defoamer, waterproof powder and water to the above mixture in sequence, stirring while adding, the water adding time is 1-2 minutes, and continue stirring for 2-3 minutes after the water is added to obtain a mixed slurry; Step 5: adding polyvinyl alcohol fiber to the mixed slurry and stirring for 2-3 minutes to obtain an initial building gypsum-based composite material; Step 6: The initial building gypsum-based composite material is molded, vibrated, formed, and cured to obtain a building gypsum high-ductility cement-based composite material.
Citation Information
Patent Citations
Environment-friendly micro-expansion high-ductility cement-based composite material and preparation method thereof
CN114349430A